Prevalence of Mental Disorders in the WHO Eastern Mediterranean Region: A Systematic Review and Meta-Analysis - Zuberi, Alina; Waqas, Ahmed; Naveed, Sadiq; Hossain, Md Mahbub; Rahman, Atif; Saeed, Khalid; Fuhr, Daniela C. (Frontiers in Psychiatry, 2021)
Objectives To synthesise the prevalence of mental and substance use disorders in countries of the Eastern Mediterranean Region (EMR) of the World Health Organization. Methods The literature search was conducted across several databases in two phases. First, we searched for systematic reviews and/or meta-analyses published before 2014, reporting prevalence estimates for mental disorders in the EMR. Then, we identified new primary cross-sectional or longitudinal studies published between 2014 to 2020. Studies were included if they had a sample size of ≥ 450 and were conducted among the general adult population. Current, period and lifetime prevalence estimates for each disorder were pooled using random-effects meta-analyses, and subgroup analyses and meta-regressions were conducted. Findings Prevalence estimates were extracted from 54 cross-sectional studies across 15 countries within the EMR. Pooled analyses of current, period and lifetime prevalence showed the highest prevalence for depression (14.8%, 95% confidence interval, CI: 10.7-20.1%), followed by generalised anxiety disorder (GAD) (10.4%, 95% CI: 7.1%-14.7%), post-traumatic stress disorder (7.2%, 95% CI: 2.9-16.6%), substance use (4.0%, 95% CI: 3.1-5.2%), obsessive compulsive disorder (2.8%, 95% CI: 1.6-4.9%), phobic disorders (1.8%, 95% CI: 1.1-2.8%), panic disorders (1.1%, 95% CI: 0.6-2.2%), bipolar disorders (0.7%, 95% CI: 0.3–1.6%) and psychosis (0.5%, 95% CI: 0.3-0.9%). Populations exposed to adverse events had higher prevalence of mental disorders than the general population. Period and lifetime prevalence showed little difference across mental disorders. More pronounced differences in prevalence were seen for depression and GAD, specifically between current and lifetime prevalence (depression: current prevalence 20.5% (95% CI: 14.9-27.4%), vs. lifetime prevalence: 4.2% (95%CI: 1.8-9.6%); GAD: current prevalence 10.3% (95% CI: 6.1-17.0), vs. lifetime prevalence: 4.5% (95% CI:2.4-8.3%). Differences between current and lifetime prevalence of mental disorders may be due to the use of different screening instruments and thresholds being applied. Conclusion The prevalence of mental and substance use disorders in the EMR is high. Despite substantial inter-survey heterogeneity, our estimates align with previous global and regional data on mental disorders. Our meta-review provides new evidence on the burden of mental health problems in the EMR.